Karakter Historis Sufisme pada Masa Klasik, Modern, dan Kontemporer - Sokhi Huda (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2017)
Sufism is an actualization of the doctrine of Tasawuf about the purification of the soul towards God as a form of realization of the Prophet’s hadith on al-iḥsān. Sufism presents three forms of activity, namely the purification of the soul, Sufi behavior, and Sufi movements. Historically, Sufism has featured a distinctive and dialectical character. Classical Sufism features five characters, namely ascetic, practical, asceticism driven by fear of God, the concept of maḥabbah, and the concept of maḥabbah for ma‘rifah. Modern Sufism features four characters, namely presentation of sharī‘ah-based Sufism with no prominent social role any longer, adaptability to modern environments, expression of new political role as a pioneer of the modern nationalist movement, expression of Sufi militancy movement in the late colonial context. Contemporary Sufism presents nine characters, namely Sufism as a variant of transnationalism, the change in the relationship of authority and pattern of association in Sufism, the emphasis of Sufism as a mean of dedication, accommodative attitude towards the new regime, Sufism as the basis of civil society for political mobilization, the development of unique forms of local voluntary associations, the solution-based attitude of Sufism in political archetype, merging of Sufism with the spirit of Salafi and political activism, and the existence of relations of globalization, transnationalism, and hybridity.